Analisa Sistem Pengendalian Keselamatan Kerja Proses Produksi Kedai Kue Dan Roti Farhana Dalam Menggunakan Metode Hirarc (Hazard Identification Risk Assessment And Risk Control) - Sumardayanti Zainuddin; Ahmad Hanafie; Rizal Syarifuddin (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2026)
Farhana pastry and bread shop is a business engaged in the production of cake and bread since 2016. During the production process, Farhana pastry and bread shop uses several machines, tools, and other raw materials. This research aims to help identify potential hazards and analyze the severity level based on danger characteristics and analyze the severity level based on the characteristics of possible hazards and carry out risk control at Farhana pastry and bread shop using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method by observing several activities carried out. Data collection was conducted through observation and interviews with the production section of Farhana Pastry and Bread Shop. The results of the study, based on interview results and risk assessment, showed that the potential hazard level was high at 28%, medium at 57%, and low at 14%.